Improving Entrepreneurship Education in Micro, Small, and Medium Enterprise Performance Based on Digital Competence and Orientation Through Competitive Advantage Mediation (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
Digital developments have encouraged culinary SME players to adapt by utilizing technology in order to compete and improve business performance. This study aims to analyze the influence of digital innovation, digital literacy, and entrepreneurial orientation on SME performance, as well as the role of competitive advantage as a mediating variable in the performance of SMEs in Malang City. This study uses a quantitative approach with proportionate purposive sampling and involves 373 respondents. Data processing was carried out using SEM-PLS through SmartPLS 4. The results show that digital innovation, digital literacy, and entrepreneurial orientation have a positive and significant effect on SME performance. Competitive advantage was found to have a positive and significant effect on SME performance and partially mediate the relationship between digital innovation, digital literacy, and entrepreneurial orientation on SME performance. This confirms that SME performance does not only depend on the ability of business actors to innovate and master technology, but also on the ability to transform the use of digital technology into competitive advantage. This study has practical implications for SME actors to develop more strategic digital strategies based on innovation, digital literacy, and entrepreneurship in order to strengthen competitiveness and business performance in a sustainable manner.